Ketentuan UUPA N0 5 Tahun 1960 Tentang Konversi Hak-Hak Atas Tanah Dalam Pembangunan - Bina Eradany (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
The land registration process requires certainty of the physical data of the land object as well as certainty of the juridical data of the land subject as well as the party providing information regarding the truth of the land ownership. The certainty of physical data and juridical data will determine the quality of the certificate product and guarantee against lawsuits from other parties who feel they own the land. Participation will be realized if the community has an understanding of the greater benefit value if their land is registered and certified. The formulation of the research problem includes: how is the conversion of land rights regulated and what are the legal consequences of the conversion of land rights. The type of research used is normative legal research. The conclusions of this research include: Regulation of conversion of land rights, including Law no. 5 of 1960 was promulgated on September 24 1960, which marked the formation of the National Land Law. One of the objectives of the promulgation of Law no. 5 of 1960 laid the foundations for establishing unity in Land Law.